Money, banking and finance - Ray, Partha (Economic & Political Weekly)
The Indian corporate bond market has remained small in size despite a long history, several committee recommendations, and continuous reforms. It is besieged by several problems ranging from illiquid... Reproduced
Keywords: Money, Banking, Finance